1991
DOI: 10.1080/10408399109527556
|View full text |Cite
|
Sign up to set email alerts
|

Microalgae as food and supplement

Abstract: The microalgae Chlorella spp., Dunaliella spp., and Scenedesmus spp., and the cyanobacteria Spirulina spp., and Aphanizomenon flos-aquae, are being used as nutrient-dense foods and sources of fine chemicals. They have significant amounts of lipid, protein, chlorophyll, carotenoids, vitamins, minerals, and unique pigments. They may also have potent probiotic compounds that enhance health. Their historical and current use are reviewed in this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
172
0
9

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 335 publications
(183 citation statements)
references
References 45 publications
2
172
0
9
Order By: Relevance
“…The last decomposition step (stage III) is mainly attributed to the decomposition of inorganic material (L贸pez-Gonz谩lez et al, 2014). It can be seen in Table 1 that SP almost has twice as much of ash content than that of CP, which is mainly due to the high alkali metal content in the feedstock (Kay, 1991). Previous studies (Liden et al, 1998;Czernik and Bridgwater, 2004) showed that sodium, potassium, magnesium and silicate in ash significantly affect pyrolysis degradation of biomass material, while potassium, sodium, calcium and magnesium are the main components influencing the combustion process.…”
Section: Combustion Characteristicsmentioning
confidence: 93%
See 1 more Smart Citation
“…The last decomposition step (stage III) is mainly attributed to the decomposition of inorganic material (L贸pez-Gonz谩lez et al, 2014). It can be seen in Table 1 that SP almost has twice as much of ash content than that of CP, which is mainly due to the high alkali metal content in the feedstock (Kay, 1991). Previous studies (Liden et al, 1998;Czernik and Bridgwater, 2004) showed that sodium, potassium, magnesium and silicate in ash significantly affect pyrolysis degradation of biomass material, while potassium, sodium, calcium and magnesium are the main components influencing the combustion process.…”
Section: Combustion Characteristicsmentioning
confidence: 93%
“…Previous studies (Liden et al, 1998;Czernik and Bridgwater, 2004) showed that sodium, potassium, magnesium and silicate in ash significantly affect pyrolysis degradation of biomass material, while potassium, sodium, calcium and magnesium are the main components influencing the combustion process. According to Kay (1991), the content of potassium, sodium, calcium and magnesium of SP is higher than that of CP. The high contents of these metals increase the rate of degradation and as a result, the maximum mass loss rate of SP is higher than that of CP for the stage III.…”
Section: Combustion Characteristicsmentioning
confidence: 99%
“…We also included in our study the cyanobacterium Spirulina maxima, widely cultivated for food and dietary supplements (38). It is worth noting here that the cyanobacteria are photosynthesizing organisms accepted to have given origin to the chloroplasts of green plants through endosymbiontic processes occurring millions of years ago.…”
Section: Discussionmentioning
confidence: 99%
“…For centuries people have been using microalgae as a food source; from China where the cyanobacteria Nostoc was used to combat famine, to another cyanobacteria Athrospira (colloquially known as Spirulina) in Chad (Kay and Barton, 1991). Despite this, it is only very, recently (the 1950's) that we began large-scale cultivation and commercial application (Spolaore et al, 2006).…”
Section: Microalgae As Foodmentioning
confidence: 99%